Relationships between power outputs measured from force-velocity test, Optojump test and Five-jump test in male shot putters - Landolsi, M.; Labiadh, L.; Zarrouk, F.; Lacouture, P.; Tabka, Z. (Science & Sports, 2015)
Purpose: The purpose was to investigate relationships between force-velocity peak power output, Optojump average power output, 5-jump relative leg length power output and shot put performance. Methods: Twelve shot putters participated in this study (n = 12, age 18.8 ± 1.5 years, weight = 96.6 ± 8.8 kg, height = 178 ± 7 cm, BMI = 30.5 ± 3.2 kg·m-2). Force-velocity peak power output, Optojump average power output and 5-jump relative leg length power output were estimated using force-velocity test, Optojump test and 5-jump test, respectively. Shot put performances were measured during a simulated competition. Results: Significant correlations were found between absolute value force-velocity peak power output (W) and leg muscle volume (r = 0.80; P < 0.01) and between force-velocity peak power output expressed relatively to body mass value and average vertical jump height (r = 0.77; P < 0.01). Shot put performance was significantly correlated with force-velocity peak power output (W) and maximal force (r = 0.81; P < 0.01; r = 0.63; P < 0.05), respectively. Optojump average power output and 5-jump relative leg length power output were not correlated to shot put performance (r = -0.25; r = 0.55), respectively. Conclusion: The correlation between force-velocity peak power output (W) and shot put performance showed that force-velocity test constitutes a useful tool assessing peak power output in shot putter athletes. Optojump test and 5-jump test seem not to be accurate for such subjects. Technical abilities and fat mass probably constitute the limiting factor in shot putter during those tests.